Does frequency of supplementation affect the performance of cattle under grazing in tropical pastures? - Sousa, Luiz Carlos Oliveira de (2022)
Our objective was to evaluate the effects of supplementation frequency on performance and voluntary intake of cattle under grazing in tropical pastures by using a meta-analytical approach. The dataset used to evaluate the voluntary intake was compiled from 18 experiments carried out in Brazil between 2009 and 2021, totaling 75 treatment means. In order to evaluate the animal performance, treatment means were collected from 19 experiments carried out in Brazil between 2003 and 2018, totaling 69 treatment means. The data were analyzed using meta-analysis techniques, considering the random effect of the experiments on the model parameters. There was no effect of supplementation (P 0.11) or supplementation frequency (P 0.18) on forage intake and dietary digested organic matter content (DOM). On the other hand, supplementation increased (P<0.01) total intake, dietary crude protein (CP) and CP-to-DOM dietary ratio. Supplementation enhanced (P<0.01) average daily gain (ADG), but without any influence of supplementation frequency (P 0.84). The ADG increased linearly (P<0.05) as forage CP increased, but no difference was detected (P>0.05) among supplementation frequencies. The additional weight gain (AWG) caused by supplementation decreased as forage CP increased and became null at 150 g CP/kg dry matter. There was a quadratic pattern (P<0.01) of the AWG in response to variations in both supplement intake and supplemental CP intake, but no effect of different frequencies was detected on this variable (P>0.05). Maximal responses occur when 5.0 g of supplement and 1.14 g of supplemental CP per kg BW were provided. Reducing supplementation frequency down to thrice a week does not affect voluntary intake and performance of cattle under grazing in tropical pastures. There is a positive response to protein supplementation on animal performance even with medium to high-quality forages. However, that response decreases as forage crude protein increases and becomes null at 150 CP/kg dry matter. Keywords: Average daily gain. N status. Protein supplementation.